Class, electoral geography and the future of UKIP: labour's secret weapon? - Mellon, J; Evans, G (Oxford University Press, 2015)
In their reply to our article Ford and Goodwin argue that UKIP's support is derived primarily from the working class, that it may become an electoral threat for Labour, particularly in Northern seats, and that since 2010 it has taken votes that would otherwise have gone to Labour. We present evidence refuting all of these claims. First, while working class voters are a little more likely to support UKIP than other classes, numerically the bulk of UKIP's support comes from the middle classes. Second, using propensity to vote scores to measure which party's supporters are likely to be fertile ground for UKIP, we find that (i) 45% of current Conservative supporters have UKIP as a second preference, compared with only 19% of Labour supporters; (ii) the potential for UKIP is slightly lower in Northern seats compared with those in the rest of England and (iii) in the absence of UKIP, far fewer of UKIP's current supporters are likely to have voted Labour (20%) than Conservative (42%). Labour has benefitted from UKIP’s presence and is likely to continue to do so.